비투스 베링 캄차카 원정대의 탐사에 관한 연구 - 李尙哲; Lee Sangchul; 朴鍾寬; Park Jongkwan (중소연구, 2022)
러시아는 16세기 중엽부터 시베리아를 개척하기 시작하였다. 1581년 본격적으로 티모페예비치 예르마크가 카자크 부대를 이끌고 시베리아로 진출하여 러시아 제국에 복속시켰다. 약 반세기 이후인 1639년 톰스크 카자크인 이반 모스크비틴은 이미 오호츠크 해안에 도착하였다. 이처럼 시베리아 정복은 영토 확장을 개시한 이후 채 1세기도 지나지 않은 짧은 기간 안에 태평양까지 도달하게 된다. 표트르 대제의 칙령으로 비투스 베링은 1725년부터 1730년까지 5년 동안 1차 캄차카 원정을 떠나 베링 해 지역 탐사를 진행하였다. 베링 원정대는 캄차카반도의 남쪽 경계선을 정확하게 규정하고 홋카이도가 캄차카와는 전혀 관계가 없다는 사실을 증명하였다. 하지만 1차 원정대는 아시아와 아메리카 대륙 사이의 바다를 직접 가로질러 항해했음에도 불구하고 직접 아메리카 대륙을 확인하지 못했다는 불완전함이 존재했다. 2차 원정 활동은 1733년부터 1742년까지 10년 동안 진행된 대규모 프로젝트였다. 베링과 치리코프는 각각 <성 표트르> 호와 <성 파벨> 호의 지휘를 맡아 베링 해협과 알래스카 및 알류샨 열도 등을 탐험하였다. 그들은 아시아와 아메리카 대륙이 육지로 하나로 연결되어 있지 않으며, 두 대륙 사이에는 해협이 존재한다는 1차 원정대의 보고서를 베링 해협을 탐사함으로써 최종적으로 증명하였다. 또한 원주민들과 직접적인 교역을 이끌어내는 데는 실패하였지만, 시베리아와 극동 및 태평양 개척의 첫발을 내딛었다는 점과 교역활동의 기반을 다졌다는 점은 높이 평가할 만하다. 그리고 탐사 과정에서 그 이전까지 서구에 알려지지 않았던 수십 개의 섬을 새로 발견하였다. 특히 아메리카 대륙 북서부에 위치한 거대한 알래스카 반도를 발견해 러시아 제국에 합병시켰다는 점은 러시아 영토 개척사에 한 획을 긋는 일이었다. Russia began to pioneer Siberia in the middle of the 16th century. In 1581, Timofeyevich Yermac led the Cossack troops into Siberia and subjugated it to the Russian Empire. About half a century later, in 1639, the Tomsk Cossack Ivan Moskvitin had already reached the coast of Okhotsk. As such, the conquest of Siberia reached the Pacific Ocean within a short period of less than a century after the territorial expansion began. By the royal order of Peter the Great, Vitus Bering left for the first Kamchatka expedition for five years from 1725 to 1730 to explore the Bering Sea area. The Bering expedition accurately defined the southern boundary of the Kamchatka Peninsula and proved that Hokkaido had no relationship with Kamchatka. However, there was an incompleteness that the 1st expedition could not directly identify the America, even though they sailed directly across the sea between Asia and the America. The second expedition was a large-scale project that lasted 10 years from 1733 to 1742. Bering and Chirikov took command of the < St. Peter > and < St. Pavel >, respectively, and explored the Bering Strait, Alaska and the Aleutian Islands. They finally proved by exploring the Bering Strait the report of the First Expedition that Asia and America are not connected by land, and there is a strait between the two continents. In addition, although it failed to induce direct trade with the natives, it is commendable for taking the first step in pioneering Siberia, the Far East and the Pacific Ocean, and for laying the foundation for trade activities. And in the course of the expedition, dozens of new islands that were previously unknown to the West were discovered. In particular, the discovery of the huge Alaska Peninsula located in the northwestern part of the Americas and annexation of it into the Russian Empire was a milestone in the history of Russian territorial pioneering.